Faktor Penentu Tax Avoidance Perusahaan Sektor Consumer Non-Cyclicals pada Masa Pandemi Covid-19 - Febrari Wati; Septian Bayu Kristanto (Juara: Jurnal Riset Akuntansi, 2023)
This study aims to examine the effect of Corporate Social Responsibility (CSR), audit committee, leverage, and company size on tax avoidance in non-cyclical consumer sector companies during the Covid-19 Pandemic. The data in this study are quantitative in nature, sourced from annual reports of companies listed on the Indonesia Stock Exchange (IDX). It can be obtained from the IDX website or from the company websites. The research model is a panel data regression. Based on the results, the CSR variable has no effect on tax avoidance. While the audit committee and company size have a negative effect on tax avoidance. As for leverage, it is proven to have a positive effect on tax evasion. This study succeeded in proving the relevance of agency theory in the practice of tax avoidance through audit committees, leverage, and firm size.